Bleeding complication after surgical removal of impacted teeth in a patient with undiagnosed clotting disorder - Hugo Leite RODRIGUES NETO; Tony Eduardo COSTA; Marcelo Galindo SILVARES; Eduardo Varela PARENTE; Daniel Amaral Alves MARLIÈRE (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT To report one case of bleeding episodes after impacted teeth extractions had been performed in a patient with undiagnosed clotting disorder, describing a sequence of approaches for hemostasis up to the appropriated diagnosis and effective resolution. A male 16-year old patient with surgical indication to remove eight impacted teeth. After the surgery, there were bleeding episodes, being needed for hospital admission to keep on his physiological functions, blood pressure and heartbeat frequency regularly, to carry out laboratory blood tests, and to achieve hemostasis by using antifibrinolytics and blood products. After 24 hours, 11% of IX clotting factor was verified into bloodstream by specific blood test, being diagnosed with mild Hemophilia B. From the diagnosis, infusions of IX clotting factor were performed to the adequate resolution and recovery of the patient. The clinical conducts were efficient to keep on stable vital signs and achieving appropriate diagnosis. However, preventive behaviors should be applied in hemophilic patients in pre- or intra-operative, avoiding circumstances that can compromise health condition of the patient.